Indications of Manipulated Financial Statements: Evidence from Indonesia State-Owned Enterprise - Sekar Mayangsari (Universitas Trisakti, 2020)
This research investigates the variables that influence manipulated financial statements. There are several fraud theories explaining these conditions, including fraud pentagon which shows six factors that might influence manipulated financial statements. This study uses state-owned entities as samples with a total of 96 non-financial firms listed during 2013-2018, all disclosing audited financial statements. The results of the study show that capability is the only factor with a positive effect on manipulated financial statements. Furthermore, the audit quality has the potential to weaken the effect of capability on manipulated financial statements.